PERAN BAPPEBTI DALAM PENGAWASAN PERDAGANGAN BERJANGKA DI PROVINSI LAMPUNG - Fitriana, Indah; Moelyono, Achmad (Jurnal Progress Administrasi Publik, 2023)
Futures trading is an alternative financial investment for individuals and businesses. The party responsible for monitoring/supervising futures trading is the Commodity Futures Trading Supervisory Agency (BAPPEBTI). The purpose of the study is to find out how the role of BAPPEBTI when supervising futures trading. This study uses qualitative descriptive research, which is a method used to describe or analyze research results but not to draw conclusions.  The subject of this study is a futures company in Lampung province. The data collection techniques used are narrative interview techniques, documentation, and data analysis. Based on the results of the study, it can be concluded that BAPPEBTI plays a role in preventive supervision carried out by means of technical training, namely in the context of developing and coaching all futures trading. The role of BAPPEBTI is to carry out repressive supervision, especially when canceling decisions of subordinate bodies that are contrary to laws and regulations. The monitoring is carried out through inspection and supervision based on standard operating procedures in order to further improve the compliance of each futures trading company. BAPPEBTI is expected to provide more intense supervision and more active direction to futures companies.   Keywords: Role; Supervision; Trade.